1996
DOI: 10.1021/ie960195c
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Organic Films from Rotating Disks Using Aqueous Solutions of Nonionic Surfactants:  Film Morphology and Cleaning Mechanisms

Abstract: In this work, we consider the cleaning of an organic liquid film, consisting initially of a concentrated solution of abietic acid in isopropyl alcohol, from the surface of a rotating disk by using aqueous solutions of a nonionic surfactant, pentaethylene glycol mono-n-dodecyl ether. The results show that the removal process takes place in three consecutive stages. The first stage is controlled by the solubilization of the abietic acid by surfactant penetration and subsequent mass transfer from the interface to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 7 publications
5
32
0
Order By: Relevance
“…In the rotating disk system, Beaudoin et al (9) and Kabin et al (11) observed that the cleaning process consisted of three successive stages. A typical cleaning curve is shown in Fig.…”
Section: Cleaning Mechanisms and Kineticsmentioning
confidence: 99%
“…In the rotating disk system, Beaudoin et al (9) and Kabin et al (11) observed that the cleaning process consisted of three successive stages. A typical cleaning curve is shown in Fig.…”
Section: Cleaning Mechanisms and Kineticsmentioning
confidence: 99%
“…From Eqs. (13)(14)(15)(16)(17), we can see that surface tension and molar volume of the entrapped fluid decreased with increased pressure. The reduction in surface (a) Net adhesion force (NAF) between spherical Cu particle and silicon surface entrapped with isopropanol medium as a function of the pressure and particle radius in CO2 + isopropanol at 313.15 K. (b) Equilibrium separation distance (ESD) between spherical Cu particle and silicon surface entrapped with isopropanol medium as a function of the pressure and particle radius in CO2 + isopropanol at 313.15 K. tension decreases the fluid bridge force F fb , while the decrease in surface tension and the molar volume of the entrapped fluid increases the capillary pressure effect force F cpe .…”
Section: Co 2 + Isopropanol Systemmentioning
confidence: 86%
“…Eqs. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were used to calculate the static forces of a particle on substrate under different pressures and temperatures. The solution of them employed Mathematica to obtain a series of data.…”
Section: Capillary Pressure Effect Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike benzoic acid, this resin is practically insoluble unless acid-base reaction ionizes the phenolic segments at the surface. The solubilization of fatty acids in aqueous detergent Ž solutions is one close parallel Chan et al, 1976;Kabin et al, . 1996 .…”
Section: Example 2: No©olak-based Photoresist Dissolutionmentioning
confidence: 92%